2023
DOI: 10.3390/foods12030472
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Application of High-Pressure Processing and Storage Time and Temperature to Sliced Iberian Chorizo

Abstract: Producing dry-cured meats with relatively high aw and pH allows companies to cut costs to the detriment of microbial control. The purpose of this study was to evaluate for the first time the effect of High Processing Pressure (HPP) and storage temperature on the microbial counts, instrumental color, oxidation and sensory characteristics of sliced Iberian chorizo with high aw and pH. First, 600 MPa was applied for 480 s to sliced chorizo with aw: 0.88 and pH: 6.01, and the treated and untreated samples were sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
6
4
0
Order By: Relevance
“…These results partially match previous results, which reported lower counts for the mesophilic bacteria and molds and yeast using 20°C than at 4°C for 120day storage in Cebo loin (Cava et al, 2021). Although there is no previous information about the effect of the storage temperature on the LAB in loin, the results (Tables 3 and 4) are generally in line with those reported in chorizo, with lower counts after storage at 20°C than at 4°C (Carrapiso et al, 2023;Martin et al, 2021;Trejo et al, 2021). The lower counts at 20°C than at 4°C in those microorganisms also matches the results for the L. monocytogenes counts in Cebo loin (Cava et al, 2021) and other dry-cured Iberian products (Cava et al, 2020(Cava et al, , 2021.…”
Section: Effect Of Storage Temperaturesupporting
confidence: 90%
See 3 more Smart Citations
“…These results partially match previous results, which reported lower counts for the mesophilic bacteria and molds and yeast using 20°C than at 4°C for 120day storage in Cebo loin (Cava et al, 2021). Although there is no previous information about the effect of the storage temperature on the LAB in loin, the results (Tables 3 and 4) are generally in line with those reported in chorizo, with lower counts after storage at 20°C than at 4°C (Carrapiso et al, 2023;Martin et al, 2021;Trejo et al, 2021). The lower counts at 20°C than at 4°C in those microorganisms also matches the results for the L. monocytogenes counts in Cebo loin (Cava et al, 2021) and other dry-cured Iberian products (Cava et al, 2020(Cava et al, , 2021.…”
Section: Effect Of Storage Temperaturesupporting
confidence: 90%
“…This partially matches previous results on Cebo loins reporting a limited effect, only significant on a* (Cava et al, 2009) or L* (Cava et al, 2021). It also matches the results found on the instrumental color, reporting no effect for Iberian chorizo (Carrapiso et al, 2023;Cava et al, 2020) and for Iberian salchichón, reporting no effect (Cava et al, 2021) or a slight effect (Ramírez et al, 2022). Conversely, a strong effect of HPP affecting both L* and a* was reported in dry-cured non-Iberian loin (Campus et al, 2008).…”
Section: Effect Of Hpp On the Loins Measured Before Storagesupporting
confidence: 89%
See 2 more Smart Citations
“…Despite lipid and protein oxidation being generally intertwined, our results showed that there was not a strong correlationship (R: 0.394, p = 0.086). Previous studies have also reported that both parameters are not always affected to the same extent by several factors in dry-cured products [ 48 , 51 ], since they measure compounds generated at different stages of the oxidation reactions. The lack of effect of the pomace on protein oxidation ( Table 3 ) matches the results from a previous study applying the same pomace to burgers, which reported no differences after 7-day storage, and an inconsistent effect before storage [ 20 ].…”
Section: Resultsmentioning
confidence: 99%